Particulate Fouling And Challenges Of Metal Foam Heat Exchangers - Shikh Anuar, Fadhilah; Malayeri, Mohammad Reza; Hooman, Kamel (Taylor and Francis Ltd., 2017)
In recent years, open-cell metal foam has gained attention for utilization for exhaust gas recirculation coolers due to its large surface area and porous structure. Theoretically, the porous foam structure would have better transfer heat through conduction and convection processes. However, the exhaust gases that enter the cooler would carry particulate matter, which may deposit within the foam structure. The existing fouling studies cannot explain the underlying mechanisms of particulate deposition thoroughly within the foam structure. This study reviews the particulate fouling of heat exchangers, particularly in the exhaust gas recirculation system. Some past approaches to investigate fouling, particle transport, and deposition in the metal foam heat exchangers for many different applications are also included. In addition, this study also includes the challenges that lie ahead in implementing the metal foam heat exchangers in the industries.